O15.3 Development of a scale measuring stigma towards alcohol abstinence among people living with HIV in vietnam. (14th July 2019) - Lancaster, Kathryn; Hetrick, Angela; Sripaipan, Teerada; Ha, Tran Viet; Quynh, Bui Xuan; Latkin, Carl; Hutton, Heidi; Chander, Geetanjali; Go, Vivian
Abstract : Background: Hazardous alcohol use is prevalent among people living with HIV (PLHIV), leading to sub-optimal HIV treatment outcomes. In Vietnam, alcohol use is highly normative making it challenging to reduce or abstain among PLHIV. We developed a quantitative scale to assess alcohol abstinence stigma (AAS) and assessed the association with alcohol use among PLHIV in Vietnam. Methods: We conducted qualitative interviews with 30 PLHIV with hazardous alcohol use from an antiretroviral therapy (ART) clinic in the Thai Nguyen to inform item development. Alcohol use was assessed using the Alcohol Use Disorders Identification Test (AUDIT). We tested items in a quantitative survey of 1, 559 ART clinic patients in Thai Nguyen to assess internal reliability (Cronbach's α) and structural validity (exploratory factor analysis, EFA). We used binomial logistic regression to estimate associations between AAS (median score >7) and alcohol use. Results: Using the results from the qualitative interview data, we developed the AAS scale with seven final items covering internalized, experience, and anticipated stigma, with scores ranging from 7 to 35. The scale had good internal consistency (α=0.75). EFA suggested the presence of two factors (r=0.42) that explained 64.5% of the total variance. Overall, the median AAS score was 7 (IQR:7–11). Those with alcohol dependence symptoms (AUDIT≥20) reported high levels of AAS (median=9, IQR:7–14) and non-harmful alcohol users (AUDIT<8) reported lower levels of AAS (median=7, IQR:7–9). AAS was significantly associated with alcohol dependency, (adjusted prevalence ratio APR =1.74, 95%CI: 1.53, 1.99), adjusting for age, gender, and employment status. Conclusion: The AAS scale may be utilized or adopted to measure of alcohol abstinence stigma among PLHIV in settings where alcohol us is culturally encouraged. This new measure will aid future studies assessing the value of developing culturally sensitive strategies to reduce alcohol consumption and ultimately improving HIV treatment outcomes among PLHIV. Disclosure: No significant relationships.